y=x^2+6x+1 and y=-2x-14

Explanation

STEP1: Find coefficients a , b and c.

In this example a=1,b=4,c=15

STEP2: Plug in the values for a, b, and c into the quadratic formula

x1,2=−b±b2−4ac−−−−−−−√2a

x1,2=−4±42−4⋅1⋅15−−−−−−−−−−√2⋅1

STEP3: Simplify expression under the square root.

x1,2=−4±−44−−−−√2

STEP4: Solve for x

x1=−4+−44−−−−√2=−2+i11−−√

x2=−4−−44−−−−√2=−2−i11−−√

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up